Casting off [large type] - Dickson, Nicole R. (Center Point Pub., 2010)
On a tiny island off the west coast of Ireland, the fishermen's handmade sweaters tell a story. Each is unique-feelings stitched into rows, memories into patterns. It is here that Rebecca Moray comes to research a book on Irish knitting. With her daughter, Rowan, accompanying her, she hopes to lose herself in the history of the island and forget her own painful past. Soon, the townsfolk's warm embrace wraps Rebecca and Rowan in a world of friendship, laughter, and love.